Implementation of Discovery Learning Module Human Circulatory System Towards Improving Students’Cognitive Learning Outcomes and Scientific Attitude - Dewi, Asmira Siska; Irfan, Zul; Wulandari, Sri (Universitas Riau, 2024)
Science learning requires learning that encourages students to discover new knowledge through exploration and investigation. This study aims to investigate the implementation of the use of discovery learning module human circulatory system towards improving student’s cognitive learning outcome and scientific attitude. The type or research used is quasi-experimental using Pretest-posttest nonequivalent control group design. The population of this study was 56 students of class VIII MTs N 2 Pekanbaru. The sample for this study consists of Class VIII A as the control group and Class VIII B as the experimental group. The data collection instrument was in the form of a cognitive learning outcome test and scientific attitude questionnaire. Data analysis was carried out by descriptive analysis and inferential analysis using the SPSS version 23 application. The results of this study indicate, the Discovery Learning-based module focusing on the human circulatory system demonstrates a positive significant impact on enhancing both cognitive learning outcomes and scientific attitudes, that there are differences in student cognitive learning outcomes and and scientific attitude between the control and experimental groups and the use of the discovery learning module human circulatory system is effectively used towards improve student’s cognitive learning outcomes and scientific attitude.